Velocity model of the Ukrainian subcrustal mantle - V. V. Gordienko; L. Ya. Gordienko (Геофизический журнал, 2018)
The purpose of this work is to calculate the velocity distribution of longitudinal seismic waves at depths of 50―100 km under the territory of Ukraine. Such a velocity model characterizes the state of the subsoil in the zones of modern activation and inactive parts of platform. The scheme of zones of modern activation, constructed earlier by results of complex geological and geophysical researches of Ukraine is used. The scheme of heat and mass transfer under the recent activation based on the advection-polymorphic hypothesis (APG) of deep processes in the Earth's tectonosphere is calculated. According to this scheme, the distribution of temperatures in the upper horizons of the mantle is calculated. By the magnitude of the temperature anomalies, in comparison with the subsoil of the platform, velocity anomalies are calculated. Partial melting of rocks was taken into account. Anomalies reach 0,3 km/s. It is shown that many of the velocity models presented in the literature are unsuitable for identifying predictive anomalies. They lack accuracy and detail. The velocity errors in the models were determined by the difference between the velocity distributions constructed for the coinciding regions. They reach 0,10―0,12 km/s. Lowering and increasing velocity are not consistent with the zones of modern activation and platform’s areas. Some local models are more accurate. The velocity distribution in its limits is consistent with the forecast for the APH in the framework of the calculation error. But they characterize only a small part of the studied territory. In addition, the variability of the velocity is very large. This is largely due to the influence of errors in the initial seismological data at relatively small distances between earthquake foci and seismic stations. Therefore, in all cases only the averaged values were used. According to seismological data for earthquakes in the territory of Ukraine and at short distances beyond its limits, averaged velocity distributions in depth for the rays crossing all known zones of modern activation are constructed. They are consistent with the forecast. On this basis, the thermal models of the upper horizons of the mantle of Ukraine are recalculated into velocity ones. Maps-slices were made at depths of 50, 75 and 100 km. The limits of velocity anomalies still need to be studied in more detail.